A Diachronic Description of the Rhetoric of the 18th Century (Филологический класс, 2022)
The article outlines the main ideas of a research project aimed to create scholarly papers and databases reflecting the formation of the Russian rhetorical tradition. Up to now, literary norms of the Russian language have been studied either in relation to syntactic structures severed from the living practice of versification, or in terms of rhetorical techniques typical of individual literary schools. The main goal of the project is not only fixing, describing and interpreting the techniques for enhancing speech embellishment and expressiveness as such and identifying the main trends in the field of composition and quantitative data about the use of tropes and figures of speech by the poets of the 18th century, but also analyzing the theoretical recommendations of the first Russian treatises on the art of eloquence, based on the rich tradition of ancient and modern European rhetorical manuals, in their correspondence with the real poetic practice of the Russian poets. The sources of the study include “De arte Rhetorica. Libri X” by F. Prokopovich, guides to eloquence by M. V. Lomonosov, some other rhetorical works of the 18th century, as well as poetic works by F. Prokopovich, A. D. Kantemir, and M. V. Lomonosov. The methods used in the course of the project research and within the framework of the interpretation of the material of this article make it possible to ensure close interaction between the linguistic, linguopoetical, linguo-stylistic and critical literary approaches to the analysis of a literary text. In the 18th century, in the era of the formation of the Russian national language and Russian literature, rhetorical culture was the only current normative basis for the formation of new general literary rules and the genre-stylistic system, and the process of trope and figure of speech unfolding in artistic text was carried out along with the expansion of the potential of the lexical and the grammatical subsystems of the language. The creation of a database that demonstrates the specific features of “rhetorical portraits” of the most famous poets and rhetoricians of the era of the Russian baroque and classicism – Feofan Prokopovich, Antioch Kantemir, Mikhail Lomonosov, Vasily Trediakovsky, Aleksandr Sumarokov – may become an important result of the project.